Pathways to literacy - Cairney, Trevor (Children, teachers, and learning., 1995)
This text recognizes that there is no simple way to develop literacy. It begins with the central premise that literacy is not simply a cognitive process, but a set of social practices used in socio-cultural contexts, and argues that literacy learners come to school with unique social histories that need to be recognised in the programmes devised to facilitate learning. Cairney claims that literacy is not a unitary social practice and suggests that there are many forms of literacy, each with specific purposes and contexts in which they are used. The author provides a look at the many practical.